Ecological and multi-level education: synergies and community building for a sustainable future - Grimaldi, Giorgio (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
Reflecting on ecological education, the contribution highlights issues, problems and proposals for a multi-level eco-sustainable conversion. Facing complex and interconnected global challenges and risks (pandemic emergencies, discrimination and exclusion, environmental and climate crises, wars and destruction, etc.), paths of coexistence and citizenship are urgently needed for the building of resilient and convivial federal communities, hinged on non-violent conflict management and the care of the commons.